New Ways of Working untuk Pembimbing Kemasyarakatan: Adaptasi Terhadap Perubahan Regulasi dan Teknologi - Mamesah, Hafizh Nuur Afif Elhadi; Anjani, Vanessa Regita; Apriliantika, Utami (Federation of Indonesian Probation Officer, 2024)
Abstract. The role of the Probation and Parole Officer in Indonesia has been expanding along with the implementation of the Law of the Republic of Indonesia No. 22 of 2022 on Corrections and the Law of the Republic of Indonesia No. 1 of 2023 on Penal Code. The change brought by these regulations requires Probation and Parole Officers to adapt to an increased workload and the challenges posed by the implementation of alternative sanctions. This paper explores the potential use of New Ways of Working, particularly in the form of digital innovation in the Probation and Parole Office (BAPAS) as a solution to optimize the role of the Probation and Parole Officer. The study employs a qualitative approach with benchmarking analysis on ten Probation and Parole Offices that have implemented digital innovations. The findings show that digital innovation has successfully increased the effectiveness and efficiency of Probation and Parole Officer’s services. However, disparities in the use of technology between different offices remain a challenge that needs to be addressed. This research recommends the development of policies to promote the adoption of best practice innovations across all Probation and Parole offices and to enhance the capacity of Probation and Parole Officers in adapting to regulatory and digital transformations. In doing so, it is expected that public service can be improved more fairly and equitably.